Robust Nonlinear Control of DFIG-Based Wind Farms for Damping Inter-Area Oscillations of Power Systems - Li, Bo; Yang, Shihai; Yang, Bin; Fang, Kaijie (Frontiers in Energy Research, 2022)
This article presents a perturbation observer–based robust nonlinear damping control (RNDC) scheme for a doubly fed induction generator (DFIG)–based wind farm to damp the inter-area oscillations of multi-area power systems. In the RNDC scheme, the perturbation term is introduced to describe the combined effects of nonlinearities, uncertainties, and disturbances of multi-area power systems with wind farms. The feedback linearization control is realized for reactive power control loops of the DFIG based on state estimation and perturbation estimation derived from a perturbation observer, thus achieving the damping control of the DFIG. The proposed RNDC scheme only needs one measurement signal, and it does not require any model parameters of the power grid and wind farm. Simulation studies are carried out on a two-area power system model connected with the wind farm to validate the control performance of the RNDC scheme under the conditions of three-phase-to-ground faults, parameter variations, and time delays.